ANALISA PERSEPSI TERHADAP SELF CARE SKILLS PADA PASIEN DM TIPE II PADA MASYARAKAT PERKOTAAN: ANALISA PERSEPSI TERHADAP SELF CARE SKILLS PADA PASIEN DM TIPE II PADA MASYARAKAT PERKOTAAN - Anita Fatarona; Andi Eka Pranata; Hendra Dwi Cahyono (Pusat Penelitian dan Pengabdian Masyarakat (PPPM) STIKES Banyuwangi, 2024)
Assessment of the impacts of urban change at the neighborhood level provides a unique opportunity to generate insights into the extent and nature of positive and negative impacts on health-related outcomes. Several specific components and mechanisms that cause urban change can influence behavior, perception and self-care, thereby impacting health. The high prevalence of non-communicable diseases, one of which is Type 2 Diabetes Mellitus. Type 2 Diabetes Mellitus occurs when the body stops producing sufficient amounts of insulin, or when the body does not use insulin properly (something known as insulin resistance). in 2021 in the Jember urban area it will reach 1,700, one of which is due to lifestyle factors in the urban environment. One strategy for dealing with type 2 diabetes mellitus is to optimize the prevention of type 2 diabetes and associated comorbidities with a therapeutic approach, one of which is optimizing self-care which can reduce complications, reduce cardiovascular and kidney risks, and improve health outcomes. The aim of this research was to determine the relationship between disease perception and the self-care skills of type II diabetes mellitus patients. This research used a cross sectional method with a total of 100 respondents, data collection used a disease perception questionnaire and a quality of life questionnaire which were given to respondents directly. The results of the chi square test research obtained a value of p = 0.030 or < (0.05), so Ha was accepted, meaning that there was a relationship between disease perception and the quality of life of type II diabetes mellitus patients. The conclusion obtained from this research is that there is a relationship between perception of illness and self-care skills. The increase in good self-care skills is due to good perception.. Keywords: Perception, Self Care Skills, Urban Society, Diabetes Mellitus